Control of the growth of bacteria vibrio harveyi by micro algae isochrysis galbana, tetraselmistetrahele and navicula sp. - Baylon, Basil C. (Iloilo City UPHSI, 2005)
Luminous bacterial disease known as vibriosis, affecting the prawn culture, is very rampant in Asian countries. Several solutions have been suggested to control vibriosis and one of these is through the use of biocontrol agents. This involves the use of microorganisms to inhibit pathogen growth, improve water quality, and stimulate the immune system of the cultured species. An experiment was conducted to determine if the three microalgae (Isochrysis galbana, Tetraselmis tetrahele, and Navicula sp.) usually found in "greenwater" can control the growth of Vibrio harveyi, a luminous bacteria that causes vibriosis. There were four treatments used: the three treatments contain microalgae and the last treatment does not contain microalga. This served as the control. In all treatments, one ml of the bacteria Vibrio harveyi was inoculated in every three replicates of every treatment. Samples were then collected daily from each flask to determine algal density count and luminous bacterial density count. The experiment lasted for seven days. Results showed that all three microalgae tested (Isochrysis galvana, Tetraselmis tetrahele, and Navicula sp.) significantly lowered the growth of Vibrio harveyi. This could be due to the bioactive substances released by the microalgae, which possibly inhibited the growth of the pathogenic bacteria Vibrio harveyi. Of the three microalgae, Navicula sp. and Tetraselmis tetrahele followed by Isochrysis galbana were found to be effective in inhibiting the growth of Vibrio harveyi.
Research II : Research Manuscripts
Keywords: Bacterias- Vibrip harveyi